FcγRIII (CD16) equips immature 6-sulfo LacNAc-expressing dendritic cells (slanDCs) with a unique capacity to handle IgG-complexed antigens - Döbel, Thomas; Kunze, Anja; Babatz, Jana; Tränkner, Katja; Ludwig, Andreas; Schmitz, Marc; Enk, Alexander; Schäkel, Knut (Blood, 2013)
Binding and uptake of immune complexes (ICs) via low-affinity Fcγ receptors (FcγRs) on dendritic cells (DCs) is well known as a booster of immune responses. It can be helpful when stimulating immunity against pathogenic microbes but may be harmful when antibodies form complexes with autologous antigens. To date, no human DC subtype specialized in handling ICs has been identified. By incubating human blood mononuclear cells with ICs and studying their cellular binding, we identified 6-sulfo LacNAc-expressing DCs (slanDCs) as having an outstanding capacity to bind ICs compared with other myeloid DCs, plasmacytoid DCs, or monocytes. Using selective blocking of different (FcγRs), we identified CD16 (FcγRIII) as the major IC-binding structure on slanDCs. In addition, CD16 proved critical for phagocytosis of IgG-coated erythrocytes, and CD16-targeted antigen led to a more efficient proliferation of CD4+ T cells than CD32 (FcγRII)-targeted antigen. Interestingly, these CD16-mediated functions are short-lived and restricted to the immature stage of slanDCs in blood. We show that CD16 is rapidly shed from the surface of maturing slanDCs, resulting from the combined action of the metalloproteinases ADAM10 and ADAM17. In conclusion, these data provide strong evidence that slanDCs play an important role in IC-driven immune responses.